Peran Interleukin-6 sebagai Faktor Prediktif Derajat Keparahan COVID-19 - Jofanka Jasmine; Diana S. Purwanto; Stefana H. M. Kaligis (Universitas Sam Ratulangi, 2022)
Abstract: The immune response to Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) critically determines the clinical course and severity of COVID-19. Several studies reported that interleukin-6 (IL-6) may be associated with the severity of COVID-19. The purpose of this study is to know and understand the role of interleukin-6 as a predictive factor in the severity of COVID-19. This research is in the form of a literature review using two databases: Pubmed and ClinicalKey. The keywords used to search for articles were Interleukin-6 OR IL-6 AND COVID-19 AND Severity OR Keparahan. After being selected based on the inclusion and exclusion criteria, 10 literatures were obtained that met the criteria. The research methods using in the literatures were retrospective and prospective study. All COVID-19 patients included in the study subjects received laboratory examinations including measurements of IL-6 levels. The results of the 10 studies used in this literature review on average show that IL-6 can be used as a predictor of severity or mortality in COVID-19 patients. In conclusion, IL-6 may play a role as a predictive factor in the severity of COVID-19.Keywords:Â COVID-19; interleukin-6; severityÂ Abstrak: Respon imun terhadap Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) secara kritis menentukan perjalanan klinis dan tingkat keparahan COVID-19. Beberapa studi melaporkan bahwa interleukin-6 (IL-6) dapat dikaitkan dengan keparahan COVID-19. Tujuan penelitian ini untuk mengetahui dan memahami peran interleukin-6 sebagai faktor prediktif derajat keparahan COVID-19. Penelitian ini berbentuk literature review menggunakan dua database, yaitu Pubmed,dan ClinicalKey. Kata kunci yang digunakan dalam pencarian artikel yaitu Interleukin-6 OR IL-6 AND COVID-19 AND Severity OR Keparahan. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi, didapatkan 10 literatur yang memenuhi kriteria. Literatur yang didapat memiliki studi retrospective dan prospective. Semua pasien COVID-19 yang termasuk dalam subjek penelitian mendapat pemeriksaan laboratorium termasuk pengukuran kadar IL-6. Hasil dari 10 studi yang digunakan dalam literature review ini rata-rata menunjukkan bahwa IL-6 dapat digunakan sebagai prediktor keparahan atau kematian pada pasien COVID-19. Sebagai simpulan, IL-6 dapat berperan sebagai faktor prediktif terhadap keparahan COVID-19.Kata kunci: COVID-19; interleukin-6; keparahan